FPGA based fault-tolerant control on an interleaved DC/DC boost converter for fuel cell electric vehicle applications. (7th December 2015) - Guilbert, Damien; Guarisco, Michael; Gaillard, Arnaud; N'Diaye, Abdoul; Djerdir, Abdesslem
Abstract: In recent years, the effects of high-frequency current ripple coming from DC/DC converters on Proton Exchange Membrane Fuel Cell (PEMFC) have gained a growing interest from the international scientific community. Currently, the durability is one of the major technical challenges to PEMFC commercialization. Basing on the existing literature, the high-frequency current ripple leads up to long-term degradations on PEMFC, particularly on its lifetime. Accordingly, in order to enhance the PEMFC lifetime, new DC/DC converter topologies have been developed, such as Interleaved DC/DC Boost Converter (IBC). Despite this topology can minimize drastically the current ripple, the loss of one leg in case of power switch fault leads up to the drastic increasing of the current ripple and consequently long-term degradations on the PEMFC. In order to cope with this issue, solutions have to be developed. Within the framework of this research work, an efficient Fault-Tolerant Control (FTC) implemented on an FPGA board has been developed to solve this issue. The latter consists in changing the PWM gate control signal according to the faulty leg given by a fault detection algorithm. The obtained experimental results between a PEMFC and an IBC topology allows demonstrating the ability of the FTC to reduce drastically the current ripple in case of power switch faults. Highlights: A brief review is given concerning fault-tolerance studies in fuel cells. Different approaches of fault-tolerance in DC/DC converters are introduced. Impacts of power switch fault on the fuel cell current ripple are illustrated. The developed fault-tolerant control has been implemented on an FPGA board. The fault-tolerant control allows minimizing the fuel cell current ripple.